Crystal structure of [{(η7-C7H7)Mo(CO)2Ga}2(μ-OGaI3){μ- OGaI(OH)2}]2·3benzene - Coombs, N; Aldridge, S; Stasch, A (2007)
The crystal structure of [{(η7-C7H7)Mo(CO)2Ga}2(μ-OGaI3){μ-OGaI(OH)2}]2·3benzene has been obtained, revealing the following properties: triclinic, space group P1 with a = 11.191(2), b = 11.468(2), c = 15.913(3)Å, α = 77.18(3), β = 76.65(3), γ = 88.53(3)°, Z = 1, R = 0.030 and wR2 = 0.058 for 7870 observed reflections [I > 2σ(I)]. The coordination geometry about the molybdenum-bound gallium centres is approximately tetrahedral with a mean Mo-Ga distance of 2.541 Å and Mo-Ga-O angles of 122.9(1) - 127.7(1)° associated with Ga(1). 2007 © The Japan Society for Analytical Chemistry.